Comparison between Rotary (Mtwo) and Manual (H-Files) Techniques for Instrumentation of Primary Teeth Root Canals - D R Murali Krishna; Jyothsna Vittoba Setty; Ila Srinivasan; Anjana Melwani (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of the study is to compare instrumentation time between manual (H-files) and rotary (Mtwo) files along with patient and operator compliance in primary lower molars. Materials and Methods: 30 primary teeth were selected and divided into two groups of 15 in each group instrumented with H-files and Mtwo files respectively. Time taken for instrumentation was calculated using stop watch. Patient and operator compliance was recorded through questionnaire. Statistical Analysis Used: Chi Square test was used to compare the distribution of teeth and number of canals. Independent Student t test was used to compare the mean time taken for instrumentation with both techniques in different canals and the mean overall time for instrumentation where P value is less than 0.001. Chi Square Goodness of Fit test was used to compare the patient's and operator's perspective regarding instrumentation techniques. Results: The instrumentation time recorded with Mtwo files is less when compared with H-files. 66.7% children preferred H-files over Mtwo, 60% children reported pain while using H-files, 60% of children were scared on sight of Mtwo rotary system. Operator could manage 80% of children easily while using H-files, but it was found that operator ease of comfort was more with Mtwo rotary system. Conclusion: Time taken for instrumentation with Mtwo files was less as compared to H-files. It was convenient for the operator to manage the child using H-files but with the use of Mtwo files, marked reduction in the instrumentation time was appreciated.